The development of the ICIQ‐UAB: A patient reported outcome measure for underactive bladder. Issue 3 (22nd February 2019) - Uren, Alan D.; Cotterill, Nikki; Harding, Christopher; Hillary, Christopher; Chapple, Christopher; Lasch, Kathryn; Stroupe, Angela; Deshpande, Chinmay; Delbecque, Laure; Van Koeveringe, Gommert; Oelke, Matthias; Belal, Mohammed; et al.
Abstract: Aims: To present the development of the International Consultation on Incontinence Questionnaire‐underactive bladder (ICIQ‐UAB) as the first patient reported outcome measure for the assessment of the symptoms and impact on the health‐related quality of life of UAB developed in‐line with the Food and Drug Administration Guidance for Industry. Methods: Draft items were developed following 44 semi‐structured concept elicitation interviews in the UK and refined using 36 cognitive interviews. A pilot study was designed to assess the draft ICIQ‐UAB's initial psychometric properties with 54 patients recruited from European hospitals. Further concept elicitation interviews were also carried out with 11 patients in the US and 10 patients in Japan. All participants had a prior urodynamic diagnosis of detrusor underactivity. Results: The cognitive interviews confirmed the initial items to be understood and interpreted as intended. Pilot testing showed that both internal consistency (Cronbach's α ≥ 0.85) and test‐retest reliability (stable patients; intraclass correlation coefficient ≥ 0.88) were high. The interviews in the US and Japan elicited symptoms and impacts that support previous findings in the UK and provided further insight into the experiences of patients in those countries. The developmental ICIQ‐UAB was refined using the evidence from all substudies. Conclusions: The validity and reliability of the ICIQ‐UAB were supported in a pilot study setting and the wider cultural applicability by the additional interviews in the US and Japan. Following further validation in future clinical trials, the developmental ICIQ‐UAB is envisaged as an important tool for the monitoring of future UAB treatment strategies.